Association between sleep duration and myopia among Chinese children during the COVID-19 pandemic: A cross-sectional study - Huang, Luoming; Chen, Xuelan; Lin, Jiajia; Fan, Xianming; Chen, Ting; Yu, Yang; Chen, Jiaxin; Hu, Jianmin (Frontiers in Public Health, 2023)
Background The studies on the association between sleep duration and myopia are limited, and the evidence is inconsistent. This study aimed to evaluate the association between sleep duration and myopia, cycloplegic spherical equivalent (SE) and axial length (AL) among Chinese children during the Corona Virus Disease 2019 (COVID-19) pandemic. Methods The study was a cross-sectional study on Chinese children aged 6–18 years. The comprehensive ophthalmic examinations for children included cycloplegic SE, AL, and standardized questionnaires. The questionnaire included sleep duration, parental myopia, outdoor time, and continuous near work duration without breaks. Myopia was defined as SE ≤-0.50 diopters (D). Results A total of 1,140 children were included in the analyses, with 84.7% of myopic children and 74.4% of children's daily sleep duration being more than 8 h/d. In univariate regression analysis, compared with sleep duration < 8 h/d, children with sleep duration of 8–9 and >9 h/d were less myopia (p < 0.01 for all), and had less myopic SE (p < 0.01 for all), and shorter AL (p < 0.01 for all). After adjusting for age, gender, parental myopia, outdoor time, and continuous near work duration without breaks, sleep duration was not associated with myopia, cycloplegic SE, and AL (p > 0.05 for all). Conclusions This study showed sleep duration was related to myopia, cycloplegic SE, and AL among Chinese children during the COVID-19 pandemic-related lifestyles, but no independent association.